Development of nonuniform transmission line protection for accurate distance protection: Computational analysis of an adaptive distance relay characteristic - Tavalaei, Jalal (John Wiley and Sons Inc., 2018)
Numerical distance relays are used in modern power system to boost the performance and reduce the computational burden of relay. Quadrilateral zone of distance relay is more suitable and capable of boundary modification on protection scheme. In this paper, an adaptive distance relay is introduced to tackle the maloperation problems encountered in non-uniform structure of combined transmission system, in which the zone 1 of distance relay is modified. Two boundaries are modified with fifth degree of polynomial equation for quadrilateral zone characteristic. Appropriate objective functions are defined to minimize the increment in relay zone, maloperation rate, and boundary accuracy error. The multiobjective optimization problem is solved by using genetic algorithm. According to the extensive computational analysis results performed by MATLAB, the high accuracy of the proposed adaptive relay was achieved. Furthermore, the proposed method has the ability to encompass all faults and tackles the influence of various power system conditions by finding the optimized equation coefficients for the nonuniform structures.